PENGARUH PENERAPAN MANAJEMEN KINERJA TERHADAP PENCAPAIAN TARGET PEKERJA KONTRAK BBOP (BRILIAN BANKING OFFICER PROGRAM) JABATAN JUNIOR ASSOCIATE MANTRI PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK REGIONAL OFFICE SURABAYA - Adi Rohman Moh Feri; Tri Kartika Pertiwi (Journal Publicuho, 2024)
The study aims to determine the Effect Of Performance Management Implementation On The Achievement Of BBOP (Brilliant Banking Officer Program) Contract Worker Target For the Junior Associate Mantri Position At Pt Bank Rakyat Indonesia (Persero) Tbk Regional Office Surabaya. Using a qualitative method with a primary data approach obtained from the BBOP Mantri Evaluation data per period. The results of the study indicate that there is a significant influence between the implementation of performance management and the achievement of worker targets, with clear goal setting, periodic feedback, and transparent performance evaluation, proven to be able to increase worker productivity and capability. This study concludes that the implementation of effective performance management is an important factor in achieving BBOP contract worker targets at PT Bank Rakyat Indonesia (Persero) Tbk Regional Office Surabaya. The recommendation from this study is for the company to continue to improve and optimize the performance management system to ensure that contract worker performance continues to increase and company targets are achieved.